Pengembangan Media Pembelajaran Berbasis Website Pada Materi Dampak Sosial Informatika (Cyberbullying) di SMPN 17 Malang - Fariz Noor Azizi; Hakkun Elmunsyah; Mira Cempaka; Aprilya Nofanti Arifin; Arya Kumara Adji; Dwi Cahya Puspita; Eka Mahendra Bagaskara; Galih Gumelar Sudi Kartomo Pamungkas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education plays a crucial role in a country's development as it serves as a means to improve the quality of human resources. Technological advancements have driven significant changes in the field of education, including the use of digital devices as learning media. At SMPN 17 Malang, the teaching of the topic